Hétérogénéité temporelle et activité de travail - Caroline Datchary; Gérald Gaglio (Revue d'anthropologie des connaissances)
In productive organizations, times, their measurement and their representations, form a cognitive framework fraught with issues, for individuals and for work collectives. The present article therefore looks at the knowledge of times, their equipping with technologies that help shape them, their polychronicity, heterogeneity and incompatibilities. Time management involves questions of production, circulation and crystallization of knowledge. Thinking about time involves singular relationships to the world and movement. This raises the question of how to study temporal heterogeneity in organizations.